Outcomes from a hybrid implementation-effectiveness study of the living well during pregnancy Tele-coaching program for women at high risk of excessive gestational weight gain - Susan de Jersey; Nina Meloncelli; Taylor Guthrie; Hilary Powlesland; Leonie Callaway; Angela T. Chang; Shelley Wilkinson; Tracy Comans; Elizabeth Eakin (BMC, 2022)
Abstract Background Excess gestational weight gain (GWG) is associated with short-term perinatal complications and longer term cardiometabolic risks for mothers and their babies. Dietitian counselling and weight gain monitoring for women at risk of high pregnancy weight gain is recommended by clinical practice guidelines. However, face-to-face appointments, during a time with high appointment burden, can introduce barriers to engaging with care. Telephone counselling may offer a solution. The Living Well during Pregnancy (LWdP) program is a dietitian-delivered telephone coaching program implemented within routine antenatal care for women at risk of excess GWG. This program evaluation used a hybrid implementation-effectiveness design guided by the RE-AIM framework to report on the primary outcomes (reach, adoption, implementation, maintenance) and secondary outcomes (effectiveness) of the LWdP intervention. Methods The LWdP program evaluation compared data from women participating in the LWdP program with a historical comparison group (pregnant women receiving dietetic counselling for GWG in the 12 months prior to the study). The primary outcomes were described for the LWdP program. Between group comparisons were used to determine effectiveness of achieving appropriate GWG and pre and post intervention comparisons of LWdP participants was used to determine changes to dietary intake and physical activity. Results The LWdP intervention group (n = 142) were compared with women in the historical comparison group (n = 49). Women in the LWdP intervention group attended 3.4 (95% CI 2.9-3.8) appointments compared with 1.9 (95% CI, 1.6-2.2) in the historical comparison group. GWG was similar between the two groups, including the proportion of women gaining weight above the Institute of Medicine recommendations (70% vs 73%, p = 0.69). Within group comparison showed that total diet quality, intake of fruit and vegetables and weekly physical activity were all significantly improved from baseline to follow-up for the women in LWdP, while consumption of discretionary food and time spent being sedentary decreased (all p < 0.05). Conclusion The LWdP program resulted in more women accessing care and positive improvements in diet quality, intuitive eating behaviours and physical activity. It was as effective as face-to-face appointments for GWG, though more research is required to identify how to engage women earlier in pregnancy and reduce appointment burden.